Predictors of attitudes towards aging in elderly living in community care - Bužgová, Radka; Kozáková, Radka; Bobčíková, Katka (BMC geriatrics, 2024)
BACKGROUND: Due to the aging of the population, the promotion of healthy aging is an important part of public health. Healthy aging of the population can be influenced by the attitudes of the elderly themselves towards old age and aging. The aim of this cross-sectional study was to find out the attitudes of older people living in a community environment toward old age and the predictors that influence these attitudes. METHODS: The evaluation of attitudes towards old age using the WHO AAQ (Attitudes to Aging Questionnaire) questionnaire involved 1,174 elderly people living in the community. Age, sex, marital status, education, subjective health assessment, social support, depression (GDS-15), anxiety (GAI), sense of coherence (SOC-13) and self-esteem (RSES) were used to evaluate related factors. RESULTS: As part of the exploratory factor analysis, a three-factor model (Psychosocial Loss, Physical Change, and Psychological Growth) was confirmed. The Cronbach alpha was found to be acceptable (α = 0.835). The predictors of better AAQ in the Psychological Loss domain were: subjective health, age, quality of life, self-esteem, sense of coherence, life satisfaction, anxiety, and social support; in the Physical Change domain: subjective health, quality of life, self-esteem, life satisfaction, cohabitation, and depression; and in the Psychological Growth domain: age, self-esteem, sense of coherence, life satisfaction, and social support. CONCLUSION: Preventive and policy measures should aim to increase the satisfaction and self-assessment of the elderly, which can help them evaluate the period of old age more positively. It is also important to create a positive perspective of ageing and elderly in society.
Keywords: Surveys and Questionnaires; Attitudes; Humans; Quality of Life; Aged; stárnutí; Attitude; senioři; lidé; Self Concept; Aging; kvalita života; průzkumy a dotazníky; Older people; sebepojetí; Cross-Sectional Studies; postoj; Quality of life; průřezové studie